Pelvic Ring Reconstruction After Iliac or Iliosacral Resection of Pediatric Pelvic Ewing Sarcoma Use of a Double-Barreled Free Vascularized Fibular Graft and Minimal Spinal Instrumentation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Background: In patients undergoing iliosacral resections, pelvic ring reconstruction can maintain stability of the pelvis and spinal column, which is expected to achieve good functional outcomes. However, no optimal reconstruction method has been established. We aimed to analyze the outcome of pelvic ring reconstruction using double-barreled free vascularized fibular graft (FVFG) and internal fixation after iliosacral resections in children. Methods: We retrospectively reviewed 16 children with pelvic Ewing sarcoma who underwent pelvic ring reconstruction using double-barreled FVFG after iliosacral resection. The fibular graft was placed between the supraacetabular region distally and the remaining ilium or sacrum proximally. The stability of the remaining pelvis and spinal column was provided by minimal spinal instrumentation. Results: Eleven Type-I and 5 Type-I+IV resections were performed for 10 boys and 6 girls, who had a mean age of 13.4 years (range, 10 to 18 years). The mean follow-up was 49.8 months (range, 28 to 96 months). At the time of the final follow-up, 14 patients were alive and 2 patients had died of disease. The mean time for bone union was 9 months (range, 6 to 12 months). Graft hypertrophy was evident in all patients at 12 months. The median Musculoskeletal Tumor Society (MSTS) score at the time of the final follow-up was 80% (range, 60% to 96.6%). Seven patients had complications. Three complications required reoperation: 1 deep infection, 1 hematoma, and 1 wound dehiscence. Three patients had disease relapse in terms of lung metastases. Conclusions: This reconstruction method can achieve a high rate of bone union and can provide good functional outcomes following resection of pediatric pelvic Ewing sarcomas with iliosacral involvement. Complications are usually manageable without a need for revision surgical procedures.
Keywords: ENDOPROSTHETIC RECONSTRUCTION; MALIGNANT-TUMORS; BONE-GRAFT; HEMIPELVIS; SALVAGE; SYSTEM; LIMB